EFFICACY OF H AND E, PAS AND MUCICARMINE IN STAINING MUCOCELE - krishnan, Preethi; Gheena; Ganapathy , Dhanraj (International Journal of Psychosocial Rehabilitation, 2019)
Introduction: Mucoceles are benign lesions related to the minor salivary glands and their respective ducts frequently affecting oral structures which are generally asymptomatic. Mucoceles are generally characterized by swollen nodular lesions preferentially located on the lower lip and differ from the so-called ranulas, which are lesions located on the floor of the mouth and related to the sublingual or submandibular glands. The prevalence of mucoceles is 2.5 lesions per 1000 population.The objective of the present study is compare to the efficacy of special staining techniques such as Mucicarmine , PAS and hematoxylin and eosin in the assessment of mucus extravasation lesion.In this study, four cases which is investigated as mucocele said were selected and stained using H and E, pas and mucicarmine. The stained slides are scored by the observers.From the study, we found that the H and E is good in staining the mucocele, pas and mucicarmine is good in staining the mucin collected in the connective tissues.